Competitive biosorption of a mixture of cationic dyes from a multicomponent solution using modified pine cone powder - Ngema, Silindile Lucia (Vaal University of Technology, 2012)
The biosorption of methyl violet and methylene blue onto modified pine cone powder was studied. Single and binary component systems studies were carried out for the biosorption of methyl violet and methylene blue onto raw, Fenton treated and acrylic acid grafted pine cone powder. Various experimental parameters were studied including initial dye concentration (200-900 mg/dm3), contact time, solution pH (4-12), mass of adsorbent (0.05-0.30g) and temperature (25-45 °C). Pseudo-first order and pseudo-second order equations were used to analyze the kinetic data. It was found that the data follow the pseudo -second order kinetic model for all temperature studied. The experimental data were analyzed using Langmuir and Freudlich isotherm model. The biosorption of methyl violet and methylene blue showed a better fit to Langmuir isotherm which properly describes the experimental data and that the sample surfaces are homogeneous. Various thermodynamic parameters, such as Gibbs energy (ΔG*), enthalpy change (ΔH*) and entropy change (ΔS*), were calculated which indicated the present system was spontaneous and exothermic process for methyl violet and methylene blue. It was found that enthalpy and entropy of acrylic acid grafted pine cone was higher as compared to raw and Fenton‘s reagent for methyl violet and methylene blue. Raw, Fenton treated and acrylic acid pine cone powder were characterized with Fourier transform infrared spectroscopy (FTIR), Ultraviolet-visible spectroscopy (UV-VIS), Thermogravimetic analysis (TGA/DTA), X-ray Diffraction (XRD) and Brauner, Emmett and Teller (BET). The following parameters were used to determine the surface properties of the grafted pine cone: change in H+ concentration and oxidation reduction potential (ORP), surface negative charge, bulk density and acid number measurements. The FTIR analysis confirmed the presence of the organic compounds on the raw, Fenton treated and acrylic acid grafted pine cone powder. The UV/VIS determined the percentage removal of dyes from aqueous solution in single and binary component systems by comparing the raw, Fenton treated and Acrylic acid grafted pine cone powder. Thermo gravimetric analysis confirmed the reactions which occur at the molecular level of the raw, Raw + KMnO4 and Fenton treated + KMnO4 pine cone powder materials. The second order derivative spectroscopy (SODS) was a suitable method for the analysis of the study of cationic dyes in binary solution. To determine the unknown concentrations of methyl violet and methylene blue dyes in binary solution using SODS, maximum wavelengths 561.8 nm and 623.1 nm were obtained. It was found that the percentage removal was higher for acrylic acid grafted pine cone than Fenton‘s treated and raw pine cone and treated samples adsorbed more methyl violet that methylene blue.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Biosorption of methyl; Biosorption of methylene; Pine cone powder; Cationic dyes; Fenton treatment; Organic compounds removal; Biological treatment processes; Dissertations, Academic -- South Africa.; Water -- Purification -- Adsorption.; Bioorganic chemistry.